DiGeorge Syndrome: Prenatal Diagnosis and Outcome in a Tertiary Care Fetal Medicine Center - Mahajan, Rahul; Elayedatt, Rinshi; Krishnan, Vivek (Journal of Fetal Medicine, 2024)
Introduction DiGeorge syndrome (DGS), caused by defects during embryonic development, is primarily sporadic and detectable via prenatal ultrasound, which reveals features like cardiovascular abnormalities and thymic hypoplasia. Early diagnosis of deletion 22q11.2 aids in effective prenatal, perinatal, and postnatal care management.Objectives The aim of this series was to delineate the common and unusual sonographic abnormalities as well as outcomes of prenatally diagnosed DiGeorge fetuses from a single tertiary care center.Methods This is a single center retrospective study of eight fetuses detected in the mid trimester between 2012 and 2020. They were evaluated extensively for anatomic anomalies on ultrasound and diagnosed deletion 22q11.2 using fluorescence in situ hybridization or microarray based comparative genomic hybridization.Results Congenital heart disease (CHD) was the primary indication for evaluation in six of eight fetuses, while one had a strong family history of DGS. The mean maternal age and gestational age were 33 years 4 months and 19 weeks 3 days, respectively. The majority (5 of 8) had conotruncal heart defects. Three of eight fetuses had extracardiac findings in varying combinations. Hypoplasia of the thymus and small for gestational age were common findings in three of eight fetuses. Lesser known associations like congenital talipes equinovarus (CTEV), choroid plexus (CP) cysts, and clenched fists with pointing index finger were noted in one fetus each, thereby expanding the fetal phenotypic spectrum. Four of eight of the families decided to terminate the pregnancy. Two of eight babies expired and the two surviving infants are doing well with near normal developmental milestones.Conclusion Though conotruncal CHD is the most consistent finding in DGS prenatally, CTEV, polyhydramnios, clenched fists with pointing index finger, and CP cyst in association with other subtle fetal markers in the absence of CHD should raise a high index of suspicion of DGS prenatally. Early and prompt diagnosis is imperative for counseling families, enabling them in decision making, and to garner knowledge about anticipatory postnatal care.
Keywords: DiGeorge syndrome; deletion 22q11.2; conotruncal defects; congenital talipes equinovarus; clenched fists; choroid plexuses cysts